Robot-Assisted Thoracoscopic Resection of a Posterior Mediastinal Mullerian Cyst. (4th February 2018) - Chao, Calvin; Vanguri, Vijay; Uy, Karl
Abstract : First described in 2005, the Mullerian derived cyst in the mediastinum is a rare finding with few subsequent reports. We report a case of Mullerian cyst occurring in the mediastinum of a 49-year-old female that was resected by robot-assisted thoracoscopic surgery. To our knowledge, this is the first report of robot-assisted resection of Hattori's cyst. Histopathologic analysis revealed ciliated Mullerian-type tubal epithelium positive for paired box gene 8 (PAX8), estrogen receptor (ER), and progesterone receptor (PR), confirming Mullerian differentiation. We also review the clinical presentation, pathology, and differential diagnosis of such cysts.